NEXUS BETWEEN OUTREACH AND PRODUCTIVITY OF MICROFINANCE IN LATIN AMERICA - Amin, Waqas; Ramirez-Asis, Edwin Hernan; Vilchez-Carcamo, Juan Emilio; Silva-Zapata, Miguel Angel; Ali, Rizwan; Gillani, Kiran Zahra (The journal of contemporary issues in business and government, 2021)
Our work aims to consider the effect of outreach on the productivity of staff working in microfinance institutions (MFIs). The study considers the panel data of Latin American countries for the period of 2006-2020. For this study, we use several techniques, including Ordinary least square (OLS), Random effect model (RE) and generalized method of momentum(GMM). Accessing poor customers is more dangerous to MFIs and harmful for staff efficiency and productivity. So, we disclosed that the influence of depth of outreach on staff productivity is negative. Whilethe breadth of outreach is found to impact staff productivity, serving better off clients positively is not risky for MFIs and improves the institution's productivity. Better off clients provide a cushion against credit risk, so MFIs are more focused on extending the loan to these clients, increasing staff productivity. GMM also present the same results. MFIs prefer to provide loan facilities to all those customers who work for, extending the staff productivity, and this technique also reduces the credit risk. Our study on the impact of MFIs outreach on its productivity is comparatively new in the microfinance field instead of others studies like impact on efficiency, sustainability and profitability.